Elastooptyczne metody wyznaczania naprężeni w polaczeniach wciskanych - Sawczenko, W.I.; Rubisz, J.J. (Engineering Transactions, 1968)
The present paper is devoted to the application of the photoelastic method to the determination of the stress produced in shrink fitted elements. The "freezing" of the model is proposed to be carried out as follows. The model of the external element is heated to a temperatute within the interval between the freezing temperature and 443°K, the model of the internal part remaining at room temperature. Then, the two parts are assembled and the temperature of the whole is brought to the freezing value. At the time of assembly the difference of temperatures may attain 150°. The method proposed has been verified for thin disc. The experimental results are in good agreement with the computation data of the plane problem of elasticity. The stress distribution is determined for a short hollow cylinder with a thick disc shrink fitted at the middle point or two thick disc at the ends and also in the case of an assembly of discs with eccentric holes.